Age-related differences in intramuscular fat distribution: spatial quantification in human ankle plantar flexors - Zhao, Zhenkai; Smith, Fiona Elizabeth; Dick, Taylor J. M.; Hodson-Tole, Emma (Frontiers in Bioengineering and Biotechnology, 2025)
IndroductionAccumulation of intramuscular fat (IMF) is an important marker of skeletal muscle health, typically reported as the mean intramuscular fat fraction (FF) from quantitative magnetic resonance imaging (MRI). However, such a summary measure does not reveal the spatial distribution of the FF through the muscle volume, and currently no methods to quantify intramuscular FF spatial distribution have been reported. This study assessed two- and three-dimensional characteristics of intramuscular FF spatial distribution and investigated age-related differences in intramuscular FF clustering in medial gastrocnemius (MG), lateral gastrocnemius (LG), and soleus (SOL) muscles.MethodsA total of 32 physically active young (N = 19, 23.8 ± 2.2 years) and older (N = 13, 70.1 ± 2.2 years) participants were recruited. Intramuscular FF regions were extracted from axial mDixon MRIs using a region-growing method, revealing branch-like clusters, potentially following the vasculature. Three-dimensional intramuscular FF clustering and density were assessed using Delaunay tessellation and Ripley’s functions.ResultsOlder adults exhibited significantly shorter Delaunay mean edge lengths compared to young (MG: 2.6 ± 0.5 mm vs. 3.2±0.4 mm, p < 0.001; LG: 2.5 ± 0.6 mm vs. 3.3 ± 0.8 mm, p < 0.001; SOL: 2.4 ± 0.4 mm vs. 3.5 ± 0.7 mm, p < 0.001), indicating denser clustering. Ripley’s K function confirmed greater clustering in older adults. Two-way ANOVA revealed aging (F statistics = 21, p < 0.001, Hedge’s g = 1.8) but not sex (F statistics = 1.5, p = 0.9, Hedge’s g = 0.3) as the main effect for variation in intramuscular FF clustering, with no interaction between these two factors (F statistics = 1.3, p = 0.35). DiscussionThis work provides an objective framework for characterizing intramuscular FF spatial distribution, providing a means to track skeletal muscle fatty replacement and provide more robust and sensitive markers of skeletal muscle health.